PEDOT: PSS thermoelectric composite film and preparation method and application thereof
By using hydrothermal method in the PEDOT:PSS thermoelectric composite film and compounding it under simulated sunlight irradiation, the problem of strong coupling of σ and S in the PEDOT:PSS thermoelectric composite film was solved, and the power factor was significantly optimized.
Patent Information
- Application Number
- CN202510118532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The strong coupling problem of electrical conductivity (σ) and Seebeck coefficient (S) in PEDOT:PSS thermoelectric composite films leads to a lower intrinsic power factor (PF).
SnO2 nanosheets were prepared by hydrothermal method and compounded with PEDOT:PSS. Ultra-low content of nanoscale SnO2 was used to recombinate with PEDOT:PSS. The decoupling of σ and S was achieved by simulating sunlight irradiation.
Without affecting the conductivity, the Seebeck coefficient is significantly improved, resulting in a significant optimization of the power factor and achieving effective decoupling of σ and S.
Smart Images

Figure CN119894344A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible thermoelectric film material preparation, and in particular relates to a PEDOT:PSS thermoelectric composite film and a preparation method and application thereof. Background Art
[0002] Thermoelectric materials are semiconductor materials that can directly convert thermal energy into electrical energy. Polymer semiconductor materials such as poly(3,4-ethylenedioxythiophene): poly(styrenesulfonic acid) (PEDOT:PSS) have the advantages of intrinsic low thermal conductivity, low cost and high mechanical flexibility, and are therefore widely studied in the field of flexible thermoelectric materials. Due to the low intrinsic thermal conductivity of polymers, their thermoelectric performance is usually measured by power factor ( PF ) to evaluate: PF = σS 2 , s and S The conductivity and Seebeck coefficient are respectively. s and low S The problem leads to the intrinsic PF Lower.
[0003] Composite inorganic second phase is a common strategy to improve the thermoelectric performance of PEDOT:PSS. The energy filtering effect generated at the interface of the two phases can usually improve the power factor, that is, filtering low-energy carriers at the interface and allowing high-energy carriers to pass through the interface of the two phases. Therefore, by selecting an inorganic composite phase with a suitable work function, the power factor can be adjusted. s and S , thereby optimizing thermoelectric performance. However, the energy filtering effect in thermoelectric composites still cannot be decoupled s and S , that is, the improvement of one parameter is at the expense of the reduction of another parameter to varying degrees. Through the balanced optimization of the two parameters, a higher power factor is finally achieved. Light is often used to improve the electronic properties of semiconductor materials, but currently, visible light or ultraviolet light cannot effectively decouple the thermoelectric composite material. s and S Two parameters (J. Appl. Phys. 114(17) (2013), Nano Energy 49 (2018), J.Mater. Chem. A 10(2) (2022), J. Mater. Chem. A 9(31) (2021)), and the above literature also has problems such as high content of composite phase making it difficult to disperse, complex preparation method, limited illumination band (visible light or ultraviolet light) resulting in limited practical application.
[0004] For the conductivity of PEDOT:PSS thermoelectric composite film ( s ) and the Seebeck coefficient ( S ), a new preparation method is needed to achieve the decoupling of conductivity and Seebeck coefficient in PEDOT:PSS thermoelectric composite films. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a PEDOT:PSS thermoelectric composite film and a preparation method and application thereof, so as to solve the problem of strong coupling between electrical conductivity and Seebeck coefficient in the PEDOT:PSS thermoelectric composite film, that is, the technical problem of improving the Seebeck coefficient without affecting the electrical conductivity.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a PEDOT:PSS thermoelectric composite film, comprising the following steps: 1) Dissolve SnCl2·H2O particles in the first portion of distilled water, stir for the first time, then add flaky NaOH, stir for the second time, perform hydrothermal reaction, centrifuge and wash, and dry for the first time to obtain SnO2 nanosheets; 2) Add polar solvent, SnO2 nanosheets and the second portion of distilled water to the PEDOT:PSS aqueous solution in sequence, and after the third stirring and oscillation, obtain a PEDOT:PSS mixed solution, and drop the PEDOT:PSS mixed solution on the substrate, and after the second drying, obtain a PEDOT:PSS composite film; 3) placing the PEDOT:PSS composite film on a hot plate, placing metal wires at both ends of the PEDOT:PSS composite film, dripping conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and after heating, the conductive silver glue solidifies, the metal wire and the PEDOT:PSS composite film are connected, and after irradiation with simulated sunlight, a PEDOT:PSS thermoelectric composite film is obtained; PEDOT:PSS thermoelectric composite film s and S Decoupling, S Increase s The decrease was less than 2%.
[0007] Preferably, in step 1), the usage ratio of SnCl2·H2O particles, the first portion of distilled water and flaky NaOH is (0.1-1) g: (10-100) mL: (0.02-1) g.
[0008] Preferably, in step 1), the first stirring rate is 500-1000 rpm, and the first stirring time is 10-60 min; the second stirring rate is 500-1000 rpm, and the second stirring time is 20-60 min.
[0009] Preferably, in step 1), the temperature of the hydrothermal reaction is 100-200 °C, and the time of the hydrothermal reaction is 12-36 h; The conditions for centrifugal washing are: using distilled water and anhydrous ethanol for several centrifugal washings respectively; The first drying temperature is 30~60 °C and the first drying time is 12~24 h.
[0010] Preferably, in step 2), the volume ratio of the PEDOT:PSS aqueous solution to the second portion of distilled water is 1:(1-5); the volume fraction of the polar solvent is 1-6 vol%; the polar solvent is DMSO, ethanol, methanol or ethylene glycol; the mass fraction of SnO2 nanosheets is 0-1 wt%.
[0011] Preferably, in step 2), the rate of the third stirring is 500-1000 rpm, and the time of the third stirring is 10-36 h; The oscillation rate is 800~4000 rpm, and the oscillation time is 1~3 h.
[0012] Preferably, in step 2), the substrate is a glass sheet, which is pre-cleaned, soaked in acetone and isopropanol in sequence, and then ultrasonicated for 15 min; the content of the PEDOT:PSS mixed solution dripped on the glass sheet is 200-1000 μL; The temperature of the second drying is 30~80 °C, and the time of the second drying is 5~24 h.
[0013] Preferably, in step 3), the metal wire is copper wire, silver wire or iron wire; The curing temperature of conductive silver glue is 80~150 °C; The power of simulated sunlight irradiation is 100~600 W, and the time is 100~500 s.
[0014] The present invention also discloses a PEDOT:PSS thermoelectric composite film, which is prepared by the above-mentioned preparation method; when the mass percentage of SnO2 nanosheets is 0-1 wt%, the Seebeck coefficient of the PEDOT:PSS thermoelectric composite film is 13.3-65.30 μV·K -1 , conductivity is 379.5~428 S·cm -1 , power factor is 7~182.5 μW·m -1 ·K -2.
[0015] The present invention also discloses the application of the PEDOT:PSS thermoelectric composite film prepared by the above-mentioned preparation method in semiconductor thermoelectric devices, temperature sensors and wearable electronic devices.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a PEDOT:PSS thermoelectric composite film and its preparation method and application. The present invention adopts ultra-low content nano-level SnO2 and PEDOT:PSS composite. The ultra-low content of the inorganic composite phase can ensure the uniformity of its dispersion. Compared with micron-level SnO2, nano-level SnO2 has a smaller band gap. Under simulated sunlight irradiation, electrons are more likely to jump from the valence band to conduction. In addition, the conduction band of nano-level SnO2 is higher than the Fermi level of PEDOT:PSS. The electrons in the SnO2 nanosheets can be quickly transferred to PEDOT:PSS, resulting in the dedoping of PEDOT:PSS electrons, so the Seebeck coefficient is greatly increased. At the same time, the conductivity of the composite film decreases by less than 2% in this process, so the decoupling of conductivity and Seebeck coefficient is achieved, and the power factor of the PEDOT:PSS thermoelectric composite film is greatly optimized. Specifically, the required SnO2 nanosheets are first prepared by a hydrothermal method. The nano-level SnO2 has better dispersibility in the PEDOT:PSS solution, which is conducive to the preparation of a more uniform and stable composite film. Ultra-low content of nano-SnO2 is directly compounded with PEDOT:PSS. SnO2 nanosheets can be well dispersed in the PEDOT:PSS solution to form a single-layer PEDOT:PSS thermoelectric composite film. The preparation method is simple and the PEDOT:PSS thermoelectric composite film can be directly compounded with PEDOT:PSS by using ultra-low content of nano-SnO2. The SnO2 nanosheets can be well dispersed in the PEDOT:PSS solution to form a single-layer PEDOT:PSS thermoelectric composite film. S Increase, while s The decline was less than 2%, which was truly achieved s and S The present invention improves the Seebeck coefficient of the organic thermoelectric film without affecting the electrical conductivity. Under simulated sunlight, the Seebeck coefficient of the composite film increases significantly, while the electrical conductivity s In fact, due to s and S There is a strong coupling relationship between them, and the optimization process always shows a trend of one parameter decreasing and the other parameter increasing, which leads to the PF The present invention successfully overcomes this problem and achieves s and S This characteristic is particularly important for the application of thermoelectric materials.
[0017] Furthermore, compared with other works, the present invention preferably uses ultra-low content nano-scale SnO2 nanosheets, with a content between 0.1 and 1 wt%, which can be well dispersed in the PEDOT:PSS solution. The SnO2 nanosheets can be replaced by other nano-scale oxides or other compounds with similar band structures or band gaps to SnO2.
[0018] Furthermore, stirring and vigorous shaking of the mixed solution are beneficial to the complete mixing of SnO2 nanosheets and PEDOT:PSS solution.
[0019] Furthermore, drying at a low temperature of 30-80 °C is beneficial to the formation of the film and increases the adhesion between the film and the glass sheet.
[0020] Furthermore, the light source used is a sunlight simulated light source, which has wider adaptability.
[0021] The present invention also discloses a PEDOT:PSS thermoelectric composite film prepared by the above preparation method; when the mass percentage of SnO2 nanosheets is 0-1 wt%, the Seebeck coefficient of the PEDOT:PSS thermoelectric composite film is 13.3-65.30 μV·K -1 , conductivity is 379.5~428 S·cm -1 , power factor is 7~182.5 μW·m -1 ·K -2 When the SnO2 nanosheet content is 0.25wt%, the PEDOT:PSS thermoelectric composite film is placed under simulated sunlight, and the Seebeck coefficient of the PEDOT:PSS thermoelectric composite film can reach up to 65.30 μV·K -1 , the power factor is 182.5 μW·m -1 ·K -2 By irradiating the PEDOT:PSS thermoelectric composite film with simulated sunlight, S Increase s The decrease was less than 2%, achieving s and S This decoupling has important theoretical and practical significance for improving and controlling the power factor of thermoelectric materials using light. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The change of Seebeck coefficient of PEDOT:PSS thermoelectric composite films with different SnO2 contents under light and darkness in the present invention; Figure 2 The conductivity of the PEDOT:PSS thermoelectric composite film with different SnO2 contents under light and darkness in the present invention is changed; Figure 3The figure shows the change of power factor of PEDOT:PSS thermoelectric composite films with different SnO2 contents under light and darkness in the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0025] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0026] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0027] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0028] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.
[0029] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0030] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0031] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0032] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0033] The present invention discloses a method for preparing a PEDOT:PSS thermoelectric composite film. The specific experimental steps are as follows: 1) Weigh 0.1-1 g of SnCl2·H2O particles and place them in a beaker. Add 10-100 mL of distilled water and stir for the first time at a rate of 500-1000 rpm for 10-60 min. Then add 0.02-1 g of flaky NaOH and stir for the second time at a rate of 500-1000 rpm for 20-60 min to obtain a mixed solution A.
[0034] 2) Place 10-50 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 100-200 °C for 12-36 h to obtain mixed solution B; centrifuge and wash mixed solution B several times with distilled water and anhydrous ethanol, respectively, and then dry to obtain the desired SnO2 nanosheets. The drying temperature of the centrifuged sample is 30-60 °C, and the drying time is 12-24 h.
[0035] 3) Add polar solvent, SnO2 nanosheets and distilled water to the PEDOT:PSS aqueous solution in sequence, stir it, and obtain mixed solution C. Vigorously oscillate the mixed solution C to make it fully uniform, and obtain PEDOT:PSS mixed solution D. Among them, the volume ratio of PEDOT:PSS aqueous solution to distilled water is 1: (1~5), the volume fraction of the added polar solvent is 1~6 vol%; the polar solvent is DMSO, ethanol, methanol or ethylene glycol, etc.; the mass fraction of the added SnO2 nanosheets is 0~1 wt%. The stirring rate is 500~1000 rpm, the stirring time is 10~36 h, the oscillation rate is 800~4000 rpm, and the oscillation time is 1~3h.
[0036] 4) PEDOT:PSS mixed solution D is added dropwise onto the prepared glass sheet, and PEDOT:PSS composite film is obtained after low temperature drying. The content of PEDOT:PSS mixed solution D added dropwise onto the glass sheet is 200-1000 μL. The low temperature drying temperature is 30-80 °C, and the drying time is 5-24 h.
[0037] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat to solidify the conductive silver glue so that the metal wire and the PEDOT:PSS composite film are connected to form a simple device. The obtained device was irradiated with simulated sunlight, and it was found through testing that S Increase sLess than 2% decrease , get s and S Decoupled PEDOT:PSS thermoelectric composite films.
[0038] The metal wire is a copper wire, a silver wire or an iron wire, the temperature for curing the silver glue is 80-150 °C, the power of the light is 100-600 W, and the light exposure time is 100-500 s.
[0039] Among them, SnCl2·H2O particles are commercial products with specifications of AR and 98%. The specific information is shown in Table 1: Table 1 Product specifications of SnCl2·H2O particles
[0040] Among them, the flake NaOH is a commercial product, with specifications of AR, 96% flake, and the specific information is shown in Table 2: Table 2 Product specifications of flake NaOH
[0041] Among them, the PEDOT:PSS aqueous solution is a commercial product with the specification of Clevious PH1000. The specific information is shown in Table 3: Table 3 Product specifications of PEDOT:PSS aqueous solution
[0042] Among them, DMSO solution is a commercial product with specification AR. Specific information is shown in Table 4: Table 4 Product specifications of DMSO solution
[0043] The PEDOT:PSS thermoelectric composite film prepared by the preparation method of the present invention has a Seebeck coefficient of up to 65.30 μV·K when the mass fraction of SnO2 is 0.25 wt% under simulated sunlight irradiation. -1 The conductivity of the composite film changed by less than 2% before and after illumination, and the conductivity after illumination was 428 S·cm -1 The final power factor is 182.5 μW·m -1 ·K -2 Under simulated sunlight, the Seebeck coefficient of the composite film increased significantly, while the conductivity changed by less than 2% before and after illumination, achieving the decoupling of conductivity and Seebeck coefficient, which has important theoretical and practical significance for using light to improve and control the power factor of thermoelectric materials.
[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] Example 1 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.113 g of SnCl2·H2O particles into a beaker and add 40 mL of distilled water. Stir for the first time at a rate of 840 rpm for 10 min. Then add 0.024 g of flaky NaOH and stir for the second time at a rate of 840 rpm for 20 min. Finally, a mixed solution A is obtained.
[0046] 2) Place 40 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 190 °C for 30 h to obtain mixed solution B. Mixed solution B is washed by centrifugation several times with distilled water and anhydrous ethanol, and then dried to obtain the desired SnO2 nanosheets. The drying temperature of the centrifuged sample is 60 °C and the drying time is 24 h.
[0047] 3) DMSO solution and distilled water were added to the PEDOT:PSS aqueous solution in sequence, and the mixture was stirred to obtain a mixed solution C. The mixed solution C was vigorously shaken to make it fully uniform, and a PEDOT:PSS mixed solution D was obtained. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:1, the volume fraction of the added DMSO was 5 vol%, the stirring rate was 840 rpm, the stirring time was 24 h, the oscillation rate was 3000 rpm, and the oscillation time was 1 h.
[0048] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried at low temperature to obtain a PEDOT:PSS composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass sheet was 1000 μL. The low temperature drying temperature was 40°C and the drying time was 5 h.
[0049] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat to solidify the conductive silver glue so that the metal wire and the PEDOT:PSS composite film are connected to form a simple device. The resulting device is then irradiated with simulated sunlight. The metal wire is a copper wire, the temperature for curing the silver glue is 100 °C, the power of the light is 500 W, and the light exposure time is 200 s.
[0050] The Seebeck coefficient of the PEDOT:PSS thermoelectric composite film prepared by the preparation method of Example 1 is 13.3 μV·K -1 , the conductivity is 394.2 S·cm -1 , the power factor is 7 μW·m -1 ·K -2 .
[0051] Example 2 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.113 g of SnCl2·H2O particles into a beaker and add 40 mL of distilled water. Stir for the first time at a rate of 840 rpm for 10 min. Then add 0.024 g of flaky NaOH and stir for the second time at a rate of 840 rpm for 20 min. Finally, a mixed solution A is obtained.
[0052] 2) Place 40 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 190 °C for 30 h to obtain mixed solution B. Wash mixed solution B with distilled water and anhydrous ethanol by centrifugation several times, and obtain the desired SnO2 nanosheets after drying. The drying temperature of the centrifuged sample is 60 °C and the drying time is 24 h.
[0053] 3) DMSO solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was oscillated vigorously to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:1, the volume fraction of the added DMSO was 5 vol%, and the mass fraction of the added SnO2 nanosheets was 0.1 wt%. The stirring rate was 840 rpm, the stirring time was 24 h, the oscillation rate was 3000 rpm, and the oscillation time was 1 h.
[0054] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried at low temperature to obtain a PEDOT:PSS composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass sheet was 1000 μL. The low temperature drying temperature was 40°C and the drying time was 5 h.
[0055] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is copper wire, the temperature for curing the silver glue is 100 °C, the light power is 500 W, and the light time is 200 s.
[0056] The Seebeck coefficient of the PEDOT:PSS thermoelectric composite film prepared by the preparation method of Example 2 is 22.4 μV·K -1 , conductivity is 402.3 S·cm -1 , the power factor is 20.2 μW·m -1 ·K -2 .
[0057] Example 3 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.113 g of SnCl2·H2O particles into a beaker and add 40 mL of distilled water. Stir for the first time at a rate of 840 rpm for 10 min. Then add 0.024 g of flaky NaOH and stir for the second time at a rate of 840 rpm for 20 min. Finally, a mixed solution A is obtained.
[0058] 2) Place 40 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 190 °C for 30 h to obtain mixed solution B. Wash mixed solution B with distilled water and anhydrous ethanol by centrifugation several times, and obtain the desired SnO2 nanosheets after drying. The drying temperature of the centrifuged sample is 60 °C and the drying time is 24 h.
[0059] 3) DMSO solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was oscillated vigorously to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:1, the volume fraction of the added DMSO was 5 vol%, and the mass fraction of the added SnO2 nanosheets was 0.25 wt%. The stirring rate was 840 rpm, the stirring time was 24 h, the oscillation rate was 3000 rpm, and the oscillation time was 1 h.
[0060] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried at low temperature to obtain a PEDOT:PSS composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass sheet was 1000 μL. The low temperature drying temperature was 40°C and the drying time was 5 h.
[0061] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is copper wire, the temperature for curing the silver glue is 100 °C, the light power is 500 W, and the light time is 200 s.
[0062] The Seebeck coefficient of the PEDOT:PSS thermoelectric composite film prepared by the preparation method of Example 3 is 65.3 μV·K -1 , conductivity is 428 S·cm -1 , the power factor is 182.5 μW·m -1 ·K -2 .
[0063] Example 4 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.113 g of SnCl2·H2O particles into a beaker and add 40 mL of distilled water. Stir for the first time at a rate of 840 rpm for 10 min. Then add 0.024 g of flaky NaOH and stir for the second time at a rate of 840 rpm for 20 min. Finally, a mixed solution A is obtained.
[0064] 2) Place 40 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 190 °C for 30 h to obtain mixed solution B. Wash mixed solution B with distilled water and anhydrous ethanol by centrifugation several times, and obtain the desired SnO2 nanosheets after drying. The drying temperature of the centrifuged sample is 60 °C and the drying time is 24 h.
[0065] 3) DMSO solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was oscillated vigorously to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:1, the volume fraction of the added DMSO was 5 vol%, and the mass fraction of the added SnO2 nanosheets was 0.5 wt%. The stirring rate was 840 rpm, the stirring time was 24 h, the oscillation rate was 3000 rpm, and the oscillation time was 1 h.
[0066] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried at low temperature to obtain a PEDOT:PSS composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass sheet was 1000 μL. The low temperature drying temperature was 40°C and the drying time was 5 h.
[0067] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is copper wire, the temperature for curing the silver glue is 100 °C, the light power is 500 W, and the light time is 200 s.
[0068] The Seebeck coefficient of the PEDOT:PSS thermoelectric composite film prepared by the preparation method of Example 4 is 37.9 μV·K -1 , conductivity is 379.5 S·cm -1 , the power factor is 54.5 μW·m -1 ·K -2 .
[0069] Example 5 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.113 g of SnCl2·H2O particles into a beaker and add 40 mL of distilled water. Stir for the first time at a rate of 840 rpm for 10 min. Then add 0.024 g of flaky NaOH and stir for the second time at a rate of 840 rpm for 20 min. Finally, a mixed solution A is obtained.
[0070] 2) Place 40 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 190 °C for 30 h to obtain mixed solution B. Wash mixed solution B with distilled water and anhydrous ethanol by centrifugation several times, and obtain the desired SnO2 nanosheets after drying. The drying temperature of the centrifuged sample is 60 °C and the drying time is 24 h.
[0071] 3) DMSO solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was vigorously shaken to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:1, the volume fraction of the added DMSO was 5 vol%, and the mass fraction of the added SnO2 nanosheets was 1 wt%. The stirring rate was 840 rpm, the stirring time was 24 h, the oscillation rate was 3000 rpm, and the oscillation time was 1 h.
[0072] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried at low temperature to obtain a PEDOT:PSS composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass sheet was 1000 μL. The low temperature drying temperature was 40°C and the drying time was 5 h.
[0073] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, heat the conductive silver glue to solidify it, and connect the metal wire and the PEDOT:PSS composite film. Irradiate it with simulated sunlight and test it. s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is copper wire, the temperature for curing the silver glue is 100 °C, the light power is 500 W, and the light time is 200 s.
[0074] The Seebeck coefficient of the PEDOT:PSS thermoelectric composite film prepared by the preparation method of Example 5 is 28.6 μV·K -1 , the conductivity is 427.3 S·cm -1 , power factor is 35 μW·m -1 ·K -2 .
[0075] Example 6 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.1 g of SnCl2·H2O particles and place them in a beaker. Add 10 mL of distilled water and stir for the first time at a rate of 500 rpm for 60 min. Then add 0.02 g of flaky NaOH and stir for the second time at a rate of 500 rpm for 60 min. Finally, a mixed solution A is obtained.
[0076] 2) Place 10 mL of mixed solution A in a hydrothermal reactor and perform a hydrothermal reaction at 100 °C for 12 h to obtain mixed solution B. Wash mixed solution B with distilled water and anhydrous ethanol by centrifugation several times, and obtain the desired SnO2 nanosheets after drying. The drying temperature of the centrifuged sample is 30 °C and the drying time is 12 h.
[0077] 3) Ethylene glycol solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was oscillated vigorously to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:2, the volume fraction of the added ethylene glycol was 1 vol%, and the mass fraction of the added SnO2 nanosheets was 0.8 wt%. The stirring rate was 500 rpm, the stirring time was 10 h, and the oscillation rate was 800 rpm, and the oscillation time was 3 h.
[0078] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried to obtain the PEDOT:PSS thermoelectric composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass was 200 μL. The low temperature drying temperature was 30 °C and the drying time was 24 h.
[0079] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is silver wire, the temperature for curing the silver glue is 80 °C, the power of the light is 100 W, and the light exposure time is 100 s.
[0080] Example 7 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 1 g of SnCl2·H2O particles and place them in a beaker. Add 100 mL of distilled water and stir for the first time at a rate of 1000 rpm for 20 min. Then add 1 g of flaky NaOH and stir for the second time at a rate of 1000 rpm for 40 min. Finally, a mixed solution A is obtained.
[0081] 2) 50 mL of mixed solution A was placed in a hydrothermal reactor for a hydrothermal reaction at 200 °C for 36 h, and finally a mixed solution B was obtained. The mixed solution B was washed by centrifugation several times with distilled water and anhydrous ethanol, and the desired SnO2 nanosheets were obtained after drying. The drying temperature of the centrifuged sample was 50 °C and the drying time was 20 h.
[0082] 3) Methanol solution, SnO2 nanosheets and distilled water were added to the PEDOT:PSS aqueous solution in sequence and stirred to obtain a mixed solution C. The mixed solution C was oscillated vigorously to make it fully uniform to obtain a PEDOT:PSS mixed solution D. Among them, the volume ratio of the PEDOT:PSS aqueous solution to distilled water was 1:5, the volume fraction of the added methanol was 6 vol%, and the mass fraction of the added SnO2 nanosheets was 0.9 wt%. The stirring rate was 1000 rpm, the stirring time was 36 h, and the oscillation rate was 4000 rpm, and the oscillation time was 2 h.
[0083] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried to obtain the PEDOT:PSS thermoelectric composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass was 800 μL. The low temperature drying temperature was 80 °C and the drying time was 20 h.
[0084] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is iron wire, the temperature for curing the silver glue is 150 °C, the power of the light is 600 W, and the light exposure time is 500 s.
[0085] Example 8 A method for preparing a PEDOT:PSS thermoelectric composite film, the specific steps are as follows: 1) Weigh 0.5 g of SnCl2·H2O particles and place them in a beaker. Add 50 mL of distilled water and stir for the first time at a rate of 600 rpm for 40 min. Then add 0.8 g of flaky NaOH and stir for the second time at a rate of 800 rpm for 50 min. Finally, a mixed solution A is obtained.
[0086] 2) 30 mL of mixed solution A was placed in a hydrothermal reactor and subjected to a hydrothermal reaction at 150 °C for 20 h to obtain mixed solution B. Mixed solution B was washed by centrifugation several times with distilled water and anhydrous ethanol, and dried to obtain the desired SnO2 nanosheets. The drying temperature of the centrifuged sample was 40 °C and the drying time was 15 h.
[0087] 3) Add ethanol solution, SnO2 nanosheets and distilled water to the PEDOT:PSS aqueous solution in sequence, stir them, and obtain mixed solution C. Vigorously oscillate the mixed solution C to make it fully uniform, and obtain PEDOT:PSS mixed solution D. Among them, the volume ratio of PEDOT:PSS aqueous solution to distilled water is 1:3, the volume fraction of ethanol added is 4 vol%, and the mass fraction of SnO2 nanosheets added is 0.7 wt%. The stirring rate is 900 rpm, the stirring time is 20 h, and the oscillation rate is 1000 rpm, and the oscillation time is 1.5 h.
[0088] 4) PEDOT:PSS mixed solution D was dripped onto the prepared glass sheet and dried to obtain the PEDOT:PSS thermoelectric composite film. The content of PEDOT:PSS mixed solution D dripped onto the glass was 500 μL. The low temperature drying temperature was 60 °C and the drying time was 15 h.
[0089] 5) Place the prepared PEDOT:PSS composite film on a hot plate, place metal wires at both ends of the PEDOT:PSS composite film, drip conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and heat the conductive silver glue to solidify the metal wire and the PEDOT:PSS composite film to form a simple device. Irradiate the obtained device with simulated sunlight and test s and S , and finally get s and S Decoupled PEDOT:PSS thermoelectric composite film. The metal wire is silver wire, the temperature for curing the silver glue is 120 °C, the power of the light is 400 W, and the light exposure time is 300 s.
[0090] See also Figure 1 The figure shows the change of Seebeck coefficient of PEDOT:PSS thermoelectric composite films with different SnO2 contents under light and darkness. It can be seen from the figure that as the SnO2 content increases from 0 wt% to 1 wt%, the Seebeck coefficient of the composite film is between 13.3 and 65.30 μV·K -1For the prepared PEDOT:PSS thermoelectric composite film, in Example 1, when the SnO2 content is 0 wt%, the Seebeck coefficient under illumination is 13.3 μV·K -1 , the Seebeck coefficient in the dark is 12.5 μV·K -1 In Example 2, when the content of SnO2 is 0.1 wt%, the Seebeck coefficient under illumination is 22.4 μV·K -1 , the Seebeck coefficient in the dark is 10.0 μV·K -1 In Example 3, when the content of SnO2 is 0.25 wt%, the Seebeck coefficient under illumination is 65.3 μV·K -1 , the Seebeck coefficient in the dark is 14.6 μV·K -1 In Example 4, when the content of SnO2 is 0.5wt%, the Seebeck coefficient under illumination is 37.9 μV·K -1 , the Seebeck coefficient in the dark is 18.6 μV·K -1 In Example 5, when the content of SnO2 is 1 wt%, the Seebeck coefficient under illumination is 28.6 μV·K -1 , the Seebeck coefficient in the dark is 16.0 μV·K -1 .
[0091] See also Figure 2 The conductivity of the PEDOT:PSS thermoelectric composite film with different SnO2 contents in the present invention changes under light and darkness. It can be seen from the figure that as the SnO2 content increases from 0 wt% to 1 wt%, the conductivity of the composite film is between 379.5 and 428 S·cm -1 For the prepared PEDOT:PSS thermoelectric composite film, in Example 1, when the SnO2 content is 0 wt%, the conductivity under illumination is 394.2 S·cm -1 , the conductivity in the dark is 395.0 S·cm -1 In Example 2, when the content of SnO2 is 0.1 wt%, the conductivity under light is 402.3 S·cm -1 , the conductivity in the dark is 402.6 S·cm -1 In Example 3, when the content of SnO2 is 0.25 wt%, the conductivity under light is 428.0 S·cm -1 , the conductivity in the dark is 430.2 S·cm -1 In Example 4, when the content of SnO2 is 0.5 wt%, the conductivity under light is 379.5 S·cm -1 , the conductivity in the dark is 382.0 S·cm -1In Example 5, when the content of SnO2 is 1 wt%, the conductivity under light is 427.3 S·cm -1 , the conductivity in the dark is 433.0 S·cm -1 .
[0092] See also Figure 3 The power factor of the PEDOT:PSS thermoelectric composite film with different SnO2 contents under light and darkness in the present invention changes. It can be seen from the figure that as the SnO2 content increases from 0 wt% to 1 wt%, the power factor of the composite film increases from 7 to 182.5 μW·m -1 ·K -2 For the prepared PEDOT:PSS thermoelectric composite film, in Example 1, when the SnO2 content is 0 wt%, the power factor under illumination is 7 μW·m -1 ·K -2 , the power factor in the dark is 6.2 μW·m -1 ·K -2 In Example 2, when the content of SnO2 is 0.1 wt%, the power factor under illumination is 20.2 μW·m -1 ·K -2 , the power factor in the dark is 4.0 μW·m -1 ·K -2 In Example 3, when the content of SnO2 is 0.25 wt%, the power factor under illumination is 182.5 μW·m -1 ·K -2 , the power factor in the dark is 9.2 μW·m -1 ·K -2 In Example 4, when the content of SnO2 is 0.5 wt%, the power factor under illumination is 54.5 μW·m -1 ·K -2 , the power factor in the dark is 13.2 μW·m -1 ·K -2 In Example 5, when the content of SnO2 is 1 wt%, the power factor under illumination is 35.0 μW·m -1 ·K -2 , the power factor in the dark is 11.1 μW·m -1 ·K -2 .
[0093] In summary, the present invention provides a method for preparing a PEDOT:PSS thermoelectric composite film, which comprises sequentially adding a polar solvent, an ultra-low content of SnO2 nanosheets and distilled water to a PEDOT:PSS aqueous solution, stirring and violently shaking the mixed solution, and then dropping the uniformly mixed solution onto a glass sheet, and obtaining a PEDOT:PSS thermoelectric composite film after drying. The composite film has a power factor of up to 182.5 μW·m under simulated sunlight. -1 ·K -2 SnO2 nanosheets were prepared by hydrothermal method and composited with PEDOT:PSS. The prepared PEDOT:PSS thermoelectric composite film was exposed to simulated sunlight. S has increased significantly, and its s The decrease was less than 2%, achieving s and S This has important theoretical and practical significance for improving and controlling the power factor of thermoelectric materials using light, and is beneficial to their application in semiconductor thermoelectric devices, temperature sensors and wearable electronic devices. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a PEDOT:PSS thermoelectric composite film, characterized in that: The following steps are involved: 1) Dissolve SnCl2·H2O particles in the first portion of distilled water, stir for the first time, then add flaky NaOH, stir for the second time, perform hydrothermal reaction, centrifuge and wash, and dry for the first time to obtain SnO2 nanosheets; 2) Add polar solvent, SnO2 nanosheets and the second portion of distilled water to the PEDOT:PSS aqueous solution in sequence, and after the third stirring and oscillation, obtain a PEDOT:PSS mixed solution, and drop the PEDOT:PSS mixed solution on the substrate, and after the second drying, obtain a PEDOT:PSS composite film; 3) placing the PEDOT:PSS composite film on a hot plate, placing metal wires at both ends of the PEDOT:PSS composite film, dripping conductive silver glue at the contact point between the metal wire and the PEDOT:PSS composite film, and after heating, the conductive silver glue solidifies, the metal wire and the PEDOT:PSS composite film are connected, and after irradiation with simulated sunlight, a PEDOT:PSS thermoelectric composite film is obtained; The PEDOT:PSS thermoelectric composite film σ and S Decoupling, S Increase σ The decrease was less than 2%.
2. The method for preparing the PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 1), the usage ratio of the SnCl2·H2O particles, the first portion of distilled water and the flaky NaOH is (0.1-1) g: (10-100) mL: (0.02-1) g.
3. The method for preparing the PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 1), the first stirring rate is 500-1000 rpm, and the first stirring time is 10-60 min; the second stirring rate is 500-1000 rpm, and the second stirring time is 20-60 min.
4. The method for preparing the PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 1), the temperature of the hydrothermal reaction is 100-200 °C, and the time of the hydrothermal reaction is 12-36 h; The centrifugal washing conditions are: using distilled water and anhydrous ethanol to perform centrifugal washing several times respectively; The first drying temperature is 30-60 °C, and the first drying time is 12-24 h.
5. The method for preparing the PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 2), the volume ratio of the PEDOT:PSS aqueous solution to the second portion of distilled water is 1:(1-5); the volume fraction of the polar solvent is 1-6 vol%; the polar solvent is DMSO, ethanol, methanol or ethylene glycol; the mass fraction of the SnO2 nanosheets is 0-1wt%.
6. The method for preparing the PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 2), the third stirring rate is 500-1000 rpm, and the third stirring time is 10-36 h; The oscillation rate is 800-4000 rpm, and the oscillation time is 1-3 h.
7. The method for preparing a PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 2), the substrate is a glass sheet, which is pre-cleaned, soaked in acetone and isopropanol in sequence, and then ultrasonicated for 15 min; the content of the PEDOT:PSS mixed solution dripped on the glass sheet is 200-1000 μL; The temperature of the second drying is 30-80 °C, and the time of the second drying is 5-24 h.
8. The method for preparing a PEDOT:PSS thermoelectric composite film according to claim 1, characterized in that: In step 3), the metal wire is copper wire, silver wire or iron wire; The curing temperature of the conductive silver paste is 80-150°C; The power of the simulated sunlight irradiation is 100-600 W, and the time is 100-500 s.
9. A PEDOT:PSS thermoelectric composite film, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8; when the mass percentage of SnO2 nanosheets is 0 to 1 wt%, the Seebeck coefficient of the PEDOT:PSS thermoelectric composite film is 13.3 to 65.30 μV·K -1 , conductivity is 379.5~428 S·cm -1 , power factor is 7~182.5 μW·m -1 ·K -2 .
10. Application of the PEDOT:PSS thermoelectric composite film prepared by the preparation method according to any one of claims 1 to 8 in semiconductor thermoelectric devices, temperature sensors and wearable electronic devices.
Citation Information
Patent Citations
Nanostructured bulk thermoelectric material
CN101904025A
Preparation method of PEDOT:PSS / Cu doped silver selenide flexible composite film with high thermoelectric performance
CN111471196A
PEDOT material, quantum dot light emitting diode and preparation method
CN114685811A
PEDOT: PSS / SWCNTs composite film and preparation method and application thereof
CN118834419A
Thermoelectric conversion material manufacturing method, thermoelectric conversion element manufacturing method, and thermoelectric conversion material modification method
JP2019036599A